Diversifying Appalachian coal-dependent economies: a case study using participatory action research for community engagement - Kelly, Amy (Kansas State University, 2017)
Economic development in Appalachia has failed to achieve socioeconomic parity with the rest of the nation, especially in coal-dependent communities. This thesis examines the history of development in the region including a case study of unincorporated former coal camps in Clearfork Valley to understand how Community Capitals Framework and Appreciative Inquiry may contribute to equitable and inclusive community development. While community capital asset investment was key to achieving results and creating additional assets in the focus community, the community often had limited access to natural, financial, built and financial capitals. Social capital was the sustaining and catalyzing asset. Community developers can play a key role in Appalachia by providing capacity, outreach, and helping communities identify and invest in their accessible capitals.
Keywords: Community development; Appalachia; Coal-dependent; Participatory action research; Community capitals framework; Appreciative inquiry